Navigating turbulent waters: The Philippines' global value chains experience amid trade wars - Adrian Mendoza (University of the Philippines, School of Economics (UPSE), 2025)
In light of recent pronouncements of tariff hikes in the United States (US) and the retaliatory responses of major economies such as China, Canada, and Mexico, this paper revisits the global value chains (GVC) experience of the Philippines amid the trade tensions between China and the US from 2018 to 2019, especially within the context of the intricate web of trade linkages in East and Southeast Asia. The inter-country input-output analysis confirms that the tariff wars generated shocks that adversely affected the GVC and overall trade performance of bystander economies in East and Southeast Asia that are not directly involved in the trade conflicts but are strongly connected to the disputing parties. Sectors directly and indirectly contributing value added to American and Chinese exports hit by tariff hikes expectedly suffered the most. However, the impact was asymmetric. Country-sector pairs with higher contribution to Chinese exports to the US were more likely to experience negative growth of overall exports in 2019. But no similar effect was traced to higher exposure to US exports to China. Moreover, the impact on the Philippines was less severe compared to bigger East and Southeast Asian economies, probably due to the country's relatively weaker direct linkages to Chinese and American GVCs. Given these results, the paper discusses the effects of distortionary tariff wars within the broader context of interconnectedness, multilateralism, and power dynamics in GVC-dominated world trade. The paper argues that restoring the stability of global trade policy is necessary to renew confidence in the world trading system and reduce the lingering uncertainty created by pre-pandemic trade conflicts. The paper also highlights some potential challenges and opportunities for the Philippines amid the resurgence of the tariff wars in 2025.
Keywords: F10; F13; F14; F60; 330; global value chains; trade wars; inter-country input-output analysis; East Asia; Southeast Asia; Philippines